Rehabilitation of simultaneous bilateral epiphysial fracture of proximal tibia in adolescent - Pires, Jennifer (BMJ Case Rep, 2018)
Simultaneous and bilateral epiphysial fracture of the proximal tibia is an extremely rare injury, with only 23 cases reported in the literature. In this paper, we present a 15-year-old adolescent with a simultaneous and bilateral epiphysial fracture of the proximal tibia in sport context (trampoline jump). He underwentsurgical repair with bilateral closed reduction and internal fixation, followed by outpatient rehabilitation programme during 4 months. There was a good functional outcome, without limitation in activities of daily living and with resumption of amateur sports activity. Since there are no guidelines described for this pathology, the authors suggest a rehabilitation protocol for bilateral epiphysial fractures of the proximal tibia that underwent surgical treatment previously and in which there were no complications in the acute phase.